1967
DOI: 10.1111/j.1550-7408.1967.tb01452.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic and Histochemical Studies of Sporozoite Formation in Plasmodium berghei*

Abstract: SYNOPSIS. Observations were made on the differentiation of fine structure during sporogonic development of Plasmodium berghei. The oocyst in the process of sporozoite formation is an encapsulated structure 30‐40 μ in diameter. It typically develops while in an extracellular position, attached to the basement membrane of the mosquito midgut and projecting into the mosquito hemocoel. Occasionally, however, ookinetes passing thru the midgut epithelial cells may become impacted within a cell so that the resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

1968
1968
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 19 publications
4
55
0
Order By: Relevance
“…stephensi and An. quadrimaculatus (Vanderberg et al 1967). The same localization was described in P. vinckei by Bafort (1971) who concluded that both mechanical pressure and physiological mechanisms play a role in the movement of oocysts to the hemocoelomic surface.…”
Section: Oocyst Developmentsupporting
confidence: 67%
See 3 more Smart Citations
“…stephensi and An. quadrimaculatus (Vanderberg et al 1967). The same localization was described in P. vinckei by Bafort (1971) who concluded that both mechanical pressure and physiological mechanisms play a role in the movement of oocysts to the hemocoelomic surface.…”
Section: Oocyst Developmentsupporting
confidence: 67%
“…Oocyst development is predominantly extracellular (Duncan et al 1960, Garnham et al 1969, Howells & Davies 1971), but occasionally occurs within the midgut epithelial cell (Vanderberg et al 1967, Bafort 1971, Beaudoin et al 1974. The ookinete usually comes to rest beneath the basal lamina 18-24 hr after the infective blood meal (Sinden 1978).…”
Section: Oocyst Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of subpellicular microtubules ranges from a band of 3 or 4 in the tiny Plasmodium falciparum merozoites to ϳ60 in the considerably larger Plasmodium ookinetes (2,3,12,26,136,156,157). In coccidian parasites (Toxoplasma and Eimeria), the subpellicular microtubules are evenly spaced beneath the periphery of the pellicle; however, in Plasmodium species, most of the microtubules occupy twothirds of the circumference and one microtubule is centered within the latter one-third of the pellicle (3,157,180). P. falciparum merozoites are an exception to this spacing generalization; they have a reduced number (three or four) of subpellicular microtubules termed f-MAST (falciparum merozoite-associated assemblage of subellicular microtubules) that extend down one side of the merozoite membrane from the apex toward the posterior (12,59).…”
Section: Microtubules In the Apicomplexa Organizationmentioning
confidence: 99%